PENGARUH EFIKASI DIRI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN RIDER PICKUP PADA PT ANDIARTA MUZIZAT (NINJA XPRESS) DI WILAYAH TANGERANG - Al Mukmin, Sultan; Susanti, Fahmi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the partial and simultaneous effects of self-efficacy and work discipline on the performance of pickup riders at PT Andiarta Muzizat (Ninja Xpress) across the Tangerang area. The research method used is quantitative, employing a survey approach through questionnaires. The sample consists of 54 respondents selected from a population of 117 pick-up riders using a simple random sampling technique based on the Slovin formula. The data were analyzed using validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing, with the assistance of SPSS version 26. Based on the analysis results, the regression equation obtained is Y = 26.078 + 0.166X₁ + 0.220X₂, indicating that the regression coefficient for self-efficacy is positive at 0.166 and the coefficient for work discipline is also positive at 0.220. This shows that both self-efficacy and work discipline variables have a positive coefficient toward the employee performance variable. The self-efficacy coefficient of 0.166 suggests that if self-efficacy increases, assuming other variables remain constant, employee performance will also increase. Similarly, the work discipline coefficient of 0.220 indicates that an increase in work discipline will lead to improved employee performance. The hypothesis test shows that the calculated F-value is greater than the F-table value (Fcount = 9.888 > Ftable = 3.19). Therefore, the null hypothesis (H₀₃) is rejected and the alternative hypothesis (Ha₃) is accepted. This indicates that self-efficacy and work discipline simultaneously have a significant effect on the performance of pickup riders at PT Andiarta Muzizat (Ninja Xpress) in the Tangerang area